Tindak Tutur dan Maksim Kesantunan Berbahasa Dalam Surat-surat Ali bin Abi Thalib Kepada Muawiyah (Studi Analisis Pragmatik) - Lukman Fajariyah (Alfaz (Arabic Literatures for Academic Zealots), 2019)
This paper aims to explore the speech acts and the modesty of the language politeness principles by Ali bin Abi Thalib in his letters to Muawiyah. In addition, to find out the meaning of using politeness in various speech acts in Ali bin Abi Thalib's letters to Muawiyah, The researcher used speech act theory (Searle) and politeness maxim that was formulated by Leech as the main analysis in this research. The findings of this study indicate that almost all the letters of Ali bin Abi Talib used indirect speech acts in the form of representative sentences, expressive sentences, commissive sentences, and declarative sentences. Each variant of these sentences contains an imperative meaning. The use of politeness maxim in language has its own benefits and meanings, which is to give varying influences to the letter reader according to the variance of politeness maxim politeness used. The impact on the reader of the letter (Muawiyah) is to convince and give consideration in order to submit to the legitimate government that is the caliphate of Ali bin Abi Talib.